2014
DOI: 10.17795/jjcdc-21704
|View full text |Cite
|
Sign up to set email alerts
|

Living Within Limits: Unpleasant Experiences From the Perspective of Patients After Cardiac Surgery, a Content Analysis Study

Abstract: Background: Cardio vascular diseases (CVDs) are the main cause of death around the world and coronary artery bypass grafting (CABG) has proven to be the most effective treatment for ischemic coronary heart diseases when other treatments are ineffective. Despite the perceived improvement in the health of patients undergoing CABG, there are problems that result from operations after they are discharged from hospital. Provision of information is an integral part of most psychological interventions. Having a clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…However, in the long run, the support process for patients with chronic disease to remain adherent to their treatment regimens can impose a burden on family members, and consequently, may lead to severe stress situations within a family (10,11). This issue not only places a great burden and stress on caregivers, yet, actually worsens patients' conditions as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the long run, the support process for patients with chronic disease to remain adherent to their treatment regimens can impose a burden on family members, and consequently, may lead to severe stress situations within a family (10,11). This issue not only places a great burden and stress on caregivers, yet, actually worsens patients' conditions as well.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that perceived social support significantly contributes to patients' physical and psychological well-being and their treatment (7)(8)(9). However, some other studies have shown that certain supportive behaviors do not contribute to patients' well-being, and instead can also damage it in some ways (10,11).…”
Section: Introductionmentioning
confidence: 99%